Trading systems, foreign direct investment and economic growth: Evidence from Asean countries - Onwuka, Kevin Odulukwe (Eurojournals, 2006)
Over a decade the regional trade relations are growing in number and scope giving rise to trade policy dilemma among the developing nations. This paper presents empirical evidence on the effect of the regional trading system along with multilateral trading system and foreign direct investment (FDI) on the economic growth of ASEAN-5 countries (namely Malaysia, Singapore, Thailand, Indonesia and the Philippines) over the period 1976 to 2002. Three measures are constructed for each trading system and fixed effects estimation technique is applied to estimate the parameters of the model. The results reveal that multilateral trading system leads to faster growth rate than the regional trading system. Most of its measures are positive and are significant. The effect of regional trading system on growth rate is rather mixed. With the exception of RTA, the measures of regional trading system are negative giving inconclusive result on direction of the effect of regional trade bloc on economic growth. The effect of FDI on growth rate is more pronounced when the country is liberalising broadly. This implies that regional groupings can be utilized as a second best alternative to improve economic growth in ASEAN economies. © EuroJournals, Inc. 2006.